Hypoglycemic Activity of Polygala erioptera (Whole Plant) in Normal and Alloxan Induced Diabetic Rats - SAMMAIAH, G.; SRIVASTAVA, R.S. (Asian Journal of Chemistry, 2010)
Investigations were carried out to find out the hypoglycemic activity of alcoholic extract of Polygala erioptera Linn, in normal and diabetic albino rats and to evaluate its probable mechanism of hypoglycemic activity if any. Oral and intraperitoneal administration of the plant produced significant hypoglycemic effect in normal as well as hyperglycemic rats. It is suggested that the hypoglycemic activity of this plant may be mediated through enhancement of peripheral metabolism of glucose and increase in insulin release.